STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENGINTERNALISASIKAN MODERASI BERAGAMADI SMPN 19 TEBO - Muhamad Azmy; Duski Samad; Muhammad Zalnur (STKIP Pesisir Selatan, 2026)
Objective: This study examines the internalization of religious moderation values among students at SMPN 19 Tebo amid increasing challenges of intolerance in educational settings. It aims to identify the strategies employed by Islamic Religious Education teachers, the moderation values promoted, and the factors influencing their implementation. Using a qualitative field research approach, data were collected through observation, interviews, and documentation involving the principal, teachers, and students. Data were analysed using the Miles, Huberman, and Saldana model, while validity was ensured through triangulation. The findings indicate that the internalized values include tolerance, national commitment, anti-violence, and accommodation of local culture. Teachers promoted these values through contextual learning, role modelling, habituation, guidance, supervision, and the strengthening of religious school culture. Supporting factors included collaboration among teachers, principal support, a conducive school environment, and community participation. Meanwhile, social media influence, negative peer interactions, diverse student characteristics, and limited parental supervision emerged as major obstacles. The study concludes that Islamic Religious Education teachers play a crucial role in fostering moderate religious attitudes through continuous learning and character development.